Academic achievement and socio-economic status: a review within context-specific models of executive function - Bryant, Lauren J. (Frontiers in Developmental Psychology, 2025)
Executive function (EF) has traditionally been conceptualized as domain-general cognitive processes that support goal-directed thought and behavior. However, recent Context-Specific models suggest that EF emerges through goal-directed assemblies of processes (e.g., beliefs, language, and content knowledge) and emphasize training EF within the same contexts it is used in applied settings. This framework also provides novel insights on the impacts of environmental factors, including socio-economic status, on EF, related academic skills, and other developmental outcomes. The present narrative review examines context-specific associations among EF, socio-economic status, and academic achievement, detailing how these theories account for the mediating role of EF among these variables. Further, I review interventions informed by these models, discussing implications for students and teachers within low-income districts.